Proceedings of the 2014 European Conference on Software Architecture Workshops 2014
DOI: 10.1145/2642803.2642825
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Model-Driven Development for Systems-of-Systems

Abstract: Software-intensive systems have become increasingly large and complex and new techniques and methodologies are necessary to deal with such complexity. Model-Driven Development (MDD) has been used to deal with complex scenarios, since software models, despite details, facilitate the visualization of the whole. Moreover, MDD has been widely recognized as a way to assure quality, reducing time and effort, and making possible the automatic transformation of models to generate source code. In this direction, softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Eight of those secondary studies use an ad hoc assessment, with custom-made criteria tailored for the specific domain those reviews are covering (Delgado et al 2013;Domínguez et al 2012;Giachetti et al 2012;Giraldo et al 2014;Hansson et al 2014;Misbhauddin and Alshayeb 2015;Mohagheghi and Dehlen 2008;Santiago et al 2012). Neto et al (2014) used guidelines (Kitchenham and Charters 2007) for the quality assessment of the included primary studies.…”
Section: Quality Evaluation Of Secondary Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of those secondary studies use an ad hoc assessment, with custom-made criteria tailored for the specific domain those reviews are covering (Delgado et al 2013;Domínguez et al 2012;Giachetti et al 2012;Giraldo et al 2014;Hansson et al 2014;Misbhauddin and Alshayeb 2015;Mohagheghi and Dehlen 2008;Santiago et al 2012). Neto et al (2014) used guidelines (Kitchenham and Charters 2007) for the quality assessment of the included primary studies.…”
Section: Quality Evaluation Of Secondary Studiesmentioning
confidence: 99%
“…Some extra findings are discussed such as to manage changeability and complexity of large and complex models, keep them consistent, and verify quality on the model level that are challenges in model-driven engineering that are not yet properly covered. Neto et al (2014) address the usage of MDE in the development of systems of systems (SoS). The authors found that UML and OCL are the most frequently reported languages used in this context.…”
Section: Summary Of Secondary Studies Contributionsmentioning
confidence: 99%
“…Literature was reviewed to identify the gaps about specification and evaluation of SoS software architecture models, and to elicit existent mechanisms, methods, models, and approaches in the state of the art about MB approaches for SoS. Results were published in a workshop paper (GRACIANO NETO et al, 2014). During the review, we identified that the application of MB methods in SoS engineering were still embryonic and could be further exploited (STEINHOGL, 2015).…”
Section: Scientific Methodologymentioning
confidence: 99%
“…Model-Based Software Engineering (MBSE) has been recommended as a response to those demands, as it comprises a software development approach that prescribes models to capture knowledge acquired from the domain, supporting the specification required for evaluation purposes (RAMOS; FERREIRA; BARCELO, 2012; RAMOS; FERREIRA; BARCELO, INCOSE, 2016). MBSE also prescribes model transformations for automating the generation of software code from abstract models, taming complexity and enabling the processing of SoS properties for specification, evaluation, verification, and validation purposes (GRACIANO NETO et al, 2014;FALKNER et al, 2016). Moreover, MBSE can also make models executable, i.e., they support the management of dynamic aspects visualized at runtime.…”
Section: Problem Statement and Justification For The Researchmentioning
confidence: 99%
See 1 more Smart Citation